Examination of heat transfer in carbon nanotube nanofluids under thermal radiation, magnetic field, and viscosity distribution - Chou, Dean; Rehman, Ali; İnç, Mustafa; Rezapour, Shahram (Springernature, 2025)
CNTs have a remarkable TC that is far higher than that of conventional materials. They greatly improve heat transfer performance when dispersed in a base fluid by increasing the fluid's total TC.Cooling systems, heat exchangers, and thermal management systems can utilize CNT nanofluids as they enhance TC, leading to more efficient heat dissipation. This work examines the effects of thermal radiation, magnetic fields, and viscous dissipation on the heat transfer characteristics of CNT nanofluids. It looks like mixing multi-walled (MWCNT) and single-walled (SWCNT) carbon nanotubes in human blood could be a great way to improve heat transfer by using the high TC of CNTs. The research used similarity transformations (STs)bto change the governing energy and momentum equations into nonlinear ODEs. The HAM solves these equations. The study looks at how magnetic fields influence the distribution of nanoparticles, which in turn affects convective heat transfer and TC. We also look at the effects of viscous dissipation, which is the change of mechanical energy into heat, and thermal radiation, which is very important when temperatures are high. We use computer simulations to look into how temperatures are distributed, how fast heat moves, and how fluids flow when there are different strengths of magnetic fields, thermal radiation, and heat loss. The results show the complicated connections between nanofluids and environmental factors. This helps us understand how to improve heat transfer in engineering and thermal management settings. The key objective of this research paper is to enhance the heat transfer rate.
Keywords: Stretching surface; Carbon nanotubes (CNT); Homotopy analysis method (HAM); Viscous dissipation